Carbon-coated zinc oxide piezoelectric catalyst, piezoelectric film, preparation method and application thereof
Through low temperature pyrolysis, the carbon-coated zinc oxide piezoelectric catalyst is synthesized and loaded onto a polymer film, which solves the problems of poor piezoelectric properties and difficulty in recycling of traditional piezoelectric catalysts, and achieves efficient piezoelectric catalytic effects and good pollutants Processing capability.
Patent Information
- Application Number
- CN202411319531.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The piezoelectric charge separation efficiency of traditional piezoelectric catalysts is low, have poor conductivity, and are difficult to recover, which is prone to secondary pollution, limiting their application in the treatment of organic pollutant wastewater.
By synthesizing a carbon-coated zinc oxide (ZnO@C) piezoelectric catalyst by one-step low-temperature pyrolysis and loading it on a hydrophilic porous polymer film, a ZnO@C piezoelectric film with excellent piezoelectric properties was prepared.
The catalyst and film material can effectively utilize the vibration energy of the water flow, convert mechanical energy into electrical energy, significantly improve the piezoelectric catalytic effect, and show good application prospects in the treatment of various organic pollutant wastewater.
Smart Images

Figure CN118847077B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric materials, and in particular to a carbon-coated zinc oxide piezoelectric catalyst, a piezoelectric film, and a preparation method and application thereof. Background Art
[0002] Among green energy and sustainable energy, hydropower is a kind of energy existing in oceans, lakes, rivers and streams. It is one of the stable, continuous and available energy sources for power generation in nature. In recent years, piezocatalysis, as a promising emerging environmental catalytic technology, has attracted extensive attention in the fields of in-situ production of H2O2, degradation of organic pollutants, sterilization and other pollutant control. Piezocatalysis can effectively use the vibration energy of water flow to convert mechanical energy into electrical energy, generating ·OH, ·O2 - , 1O2 and other active oxygen to remove pollutants. So far, hundreds of inorganic and organic pollutants have been found to be treated by piezoelectric catalytic oxidation, which shows the broad prospects of piezoelectric catalytic degradation in pollution control.
[0003] In order to promote the development of piezoelectric catalysis, many piezoelectric catalysts have been designed, such as ZnO, MoS2, BaTiOs, Bi2Fe4O5, etc. Among them, ZnO, as a "green" piezoelectric material with biocompatibility, biodegradability and non-toxicity, has extremely high applicability. However, the piezoelectric charge separation efficiency of ZnO is low, its electrical conductivity is poor, and the generated carrier recombination rate is fast, which seriously limits its piezoelectric catalytic effect. Excellent flexibility and piezoelectric properties are two important factors for piezoelectric materials to produce good piezoelectric potential. Although traditional inorganic piezoelectric materials have higher piezoelectric coupling coefficients than organic piezoelectric materials, they are driven by weak forces and are not easy to deform due to the small energy output of flowing water. In addition, the reaction conditions for preparing piezoelectric catalytic materials by traditional methods are harsh and there is a potential problem of secondary pollution.
[0004] Therefore, it is of great significance to provide a piezoelectric catalyst and a piezoelectric film so that they can effectively utilize water energy to treat wastewater with various organic pollutants and solve the problems that traditional piezoelectric catalysts are difficult to recycle and easily generate secondary pollution. Summary of the invention
[0005] In view of this, it is necessary to provide a carbon-coated zinc oxide piezoelectric catalyst, piezoelectric film and its preparation method and application to address the above problems. The present invention synthesizes a carbon-coated zinc oxide (ZnO@C) piezoelectric catalyst by one-step low-temperature pyrolysis, optimizes the morphology and carbon coating of the ZnO@C piezoelectric catalyst by regulating temperature and time, and the catalyst preparation method is simple and has excellent piezoelectric properties; the present invention loads the ZnO@C piezoelectric catalyst on a hydrophilic porous polymer film to obtain a Zno@C piezoelectric film, which has a porous structure, good hydrophilic properties, and certain impact resistance. It can effectively use the vibration energy of water flow to convert mechanical energy into electrical energy, and can be used to treat wastewater containing a variety of organic pollutants, and has good application prospects in the field of wastewater remediation.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a carbon-coated zinc oxide piezoelectric catalyst, comprising the following steps: uniformly grinding zinc acetate dihydrate, then transferring it to an alumina crucible, annealing it in a muffle furnace at a certain temperature and time, and grinding it again after taking it out.
[0008] Furthermore, the annealing temperature is 300°C to 500°C.
[0009] Furthermore, the annealing time is 60 min to 200 min.
[0010] In a second aspect, the present invention provides a carbon-coated zinc oxide piezoelectric catalyst prepared by the above-mentioned method for preparing a carbon-coated zinc oxide piezoelectric catalyst.
[0011] Furthermore, the morphologies of zinc oxide piezoelectric catalysts include nanowires, nanospheres, nanorods and nanosheets.
[0012] In a third aspect, the present invention provides a method for preparing a carbon-coated zinc oxide piezoelectric film, comprising the following steps: adding the above-mentioned carbon-coated zinc oxide piezoelectric catalyst to a casting liquid and stirring to obtain a mixture, injecting the mixture into a glass dish, performing a phase inversion using deionized water, and then taking out the film, rinsing it, and vacuum drying it.
[0013] Furthermore, the casting solution is prepared by dissolving the precursor in an organic solvent, and adding a hydrophilic agent and a porogen to form a uniform colloid.
[0014] Preferably, the precursor includes powdered polyvinylidene fluoride, polytetrafluoroethylene, chitosan or sodium alginate.
[0015] Preferably, the hydrophilic agent includes polyvinyl pyrrolidone type hydrophilic additives, modified silane type hydrophilic additives, hydrophilic polymer type additives and hydrophobic group-introduced hydrophilic additives.
[0016] Preferably, the porogen includes polyethylene glycol, hydroxypropyl cellulose, polyurethane and urea.
[0017] Furthermore, the mass concentration of the carbon-coated zinc oxide piezoelectric catalyst added is 5% to 30%, that is, the mass percentage of the carbon-coated zinc oxide piezoelectric catalyst in the mixture is 5% to 30%.
[0018] Furthermore, the vacuum drying temperature is 50-90°C and the time is 12-24 hours.
[0019] In a fourth aspect, the present invention provides a carbon-coated zinc oxide piezoelectric film prepared by the above preparation method.
[0020] In a fifth aspect, the present invention provides a method for preparing the above-mentioned carbon-coated zinc oxide piezoelectric catalyst, a carbon-coated zinc oxide piezoelectric catalyst, a method for preparing a carbon-coated zinc oxide piezoelectric film, or the application of a carbon-coated zinc oxide piezoelectric film in the field of membrane separation and piezoelectric catalysis technology.
[0021] The beneficial effects of the present invention are:
[0022] (1) The present invention synthesizes a carbon-coated zinc oxide (ZnO@C) piezoelectric catalyst by one-step low-temperature pyrolysis, and optimizes the morphology and carbon coating layer of the ZnO@C piezoelectric catalyst by regulating temperature and time. The catalyst preparation method is simple and has excellent piezoelectric properties.
[0023] (2) The present invention loads the ZnO@C piezoelectric catalyst on a hydrophilic porous polymer film to obtain a Zno@C piezoelectric film. The piezoelectric film has a porous structure, good hydrophilicity, and certain impact resistance. It can effectively use the vibration energy of water flow to convert mechanical energy into electrical energy. It can be used to treat wastewater containing various organic pollutants and has good application prospects in the field of wastewater remediation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the ZnO@C piezoelectric catalyst prepared in Example 1 of the present invention;
[0025] Figure 2 This is a SEM image of the ZnO@C piezoelectric catalyst prepared in Example 2 of the present invention;
[0026] Figure 3 SEM image of the ZnO@C piezoelectric catalyst prepared in Example 3 of the present invention;
[0027] Figure 4 SEM image of the ZnO@C piezoelectric catalyst prepared in Example 4 of the present invention;
[0028] Figure 5SEM image of the ZnO@C piezoelectric catalyst prepared in Example 5 of the present invention;
[0029] Figure 6 SEM image of the ZnO@C piezoelectric film prepared in Example 6 of the present invention;
[0030] Figure 7 SEM image of the ZnO@C piezoelectric catalyst prepared in Comparative Example 1 of the present invention;
[0031] Figure 8 SEM image of the ZnO@C piezoelectric catalyst prepared in Comparative Example 2 of the present invention;
[0032] Fig. 9 The electrochemical impedance spectra of the ZnO@C catalysts prepared in Examples 1 to 3 and Comparative Example 2 of the present application;
[0033] Fig.10 This is a diagram showing the effect of piezoelectric catalytic degradation of tetracycline by ZnO@C catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2 of the present application;
[0034] Fig.11 This is a diagram showing the effect of piezoelectric catalytic degradation of tetracycline by the ZnO@C piezoelectric film prepared in Example 6 of the present application at different flow rates. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further clearly and completely described in combination with the embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0037] In the present invention, “carbon-coated zinc oxide” is expressed as “ZnO@C”. Example 1
[0038] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0039] 2 g of zinc acetate dihydrate was ground for 15 min, then transferred to an alumina crucible, annealed in a muffle furnace at 300 °C for 60 min, and then taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows: Figure 1As shown, the morphology is nanowire-like and well dispersed. Example 2
[0040] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0041] 2 g of zinc acetate dihydrate was ground for 15 min, then transferred to an alumina crucible, annealed in a muffle furnace at 300 °C for 90 min, and then taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows: Figure 2 As shown, most of them are in the form of nanowires, with a small number of nanosheets. Example 3
[0042] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0043] 2 g of zinc acetate dihydrate was ground for 15 min, then transferred to an alumina crucible, annealed in a muffle furnace at 300 °C for 120 min, and then taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows: Figure 3 As shown, the morphology is mostly nanowires, with a small portion being nanosheets. Example 4
[0044] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0045] 2 g of zinc acetate dihydrate was ground for 15 min, then transferred to an alumina crucible, annealed in a muffle furnace at 350 °C for 60 min, and then taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows: Figure 4 As shown, at this time, the catalyst is in the form of nanowires and is well dispersed. Example 5
[0046] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0047] 2 g of zinc acetate dihydrate was ground for 15 min, then transferred to an alumina crucible, annealed in a muffle furnace at 400 °C for 60 min, and then taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows: Figure 5 As shown, at this time, the catalyst is in the form of nanowires and is well dispersed. Example 6
[0048] A method for preparing a carbon-coated zinc oxide piezoelectric film comprises the following steps: taking 1.5 g of the carbon-coated zinc oxide piezoelectric catalyst prepared in Example 1, adding it to a casting solution, stirring for 12 hours to obtain a mixture, taking 2 ml of the mixture and injecting it into a glass dish, spraying deionized water evenly through a spray bottle for phase conversion, then taking out the film, rinsing it with deionized water, and drying it in a vacuum drying oven at 60° C. for 4 hours. The casting solution is prepared by: dissolving 0.5 g of PVDF in 8 mL of DMF, stirring continuously at 80° C. for 2 hours; then adding 0.4 mL of PEG and 0.04 g of PVP to the above mixed solution, stirring for 1 hour, and forming a uniform film solution.
[0049] The morphology of the prepared piezoelectric film is shown in Figure 6 As shown, it can be seen that the ZnO@C piezoelectric catalyst is uniformly and firmly dispersed on the PVDF substrate, and the ZnO@C piezoelectric film has a rich porous structure and a large specific surface area.
[0050] Comparative Example 1
[0051] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0052] 2 g of zinc acetate dihydrate was ground for 15 minutes and then transferred to an alumina crucible. The crucible was then annealed in a muffle furnace at a set temperature of 300 °C for 30 min, taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows Figure 7 As shown, the catalyst is in block form and has no fixed shape.
[0053] Comparative Example 2
[0054] A method for preparing a ZnO@C piezoelectric catalyst comprises the following steps:
[0055] 2 g of zinc acetate dihydrate was ground for 15 min, then transferred to an alumina crucible, annealed in a muffle furnace at 250 °C for 60 min, and then taken out and ground after cooling; the morphology of the prepared ZnO@C piezoelectric catalyst is as follows: Figure 8 As shown, the catalyst is severely agglomerated and has no fixed shape.
[0056] Performance Testing
[0057] (1) Electrochemical impedance spectroscopy of ZnO@C catalyst
[0058] The electrochemical impedance spectroscopy test was performed on the ZnO@C catalysts prepared in Example 1, Example 2, Example 3 and Comparative Example 1 using a CHI-660e electrochemical workstation. The prepared catalyst was coated on FTO glass as a working electrode, and a Pt plate and an Ag / AgCl electrode were used as a counter electrode and a reference electrode, respectively. The electrolyte used in the experiment was a 0.5 mol / L sodium sulfate solution, the operating voltage was 10 V, and the frequency range was 1-100000 Hz. The electrochemical impedance spectroscopy obtained by the test is as follows: Fig. 9 As shown. Fig. 9 It can be seen that the semicircle radius of the ZnO@C nanowire sample (Comparative Example 1) annealed at 300°C for 30 minutes is the largest, indicating that its charge transfer resistance is relatively high. The impedance of the ZnO@C catalyst with a fixed morphology (nanowire / nanosheet) prepared by Examples 1-3 is significantly reduced, the charge transfer efficiency is relatively high, and the diffusion speed is relatively fast, which is more conducive to its piezoelectric catalytic effect.
[0059] (2) Performance test of piezoelectric catalytic degradation of tetracycline by ZnO@C catalyst
[0060] Tetracycline was piezoelectrically degraded using the ZnO@C catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2. The specific steps are as follows: 100 mg of the ZnO@C catalyst prepared in different examples was added to 100 mL of tetracycline solution (10 mM), stirred at a low speed for 15 minutes to reach absorption equilibrium, and then placed in an ultrasonic instrument for piezoelectric degradation. Samples were taken at 1, 3, 5, 10, 20 and 30 minutes respectively. The absorbance of TC in the solution was measured at a wavelength of 355 nm using an ultraviolet-visible spectrophotometer (SDPTOP, UV2400). Fig.10 From the results of (a), it can be seen that the catalyst prepared in comparative example 1 has no fixed morphology and has basically no catalytic effect under the action of ultrasound, while the ZnO@C catalysts with fixed morphology (nanowires / nanosheets) prepared in examples 1-3 have significant piezoelectric catalytic effect, which proves that under constant temperature, adjusting the annealing time can improve the piezoelectric catalytic effect by controlling the morphology of the ZnO@C catalyst. Fig.10 From the results of (b), it can be seen that the catalyst prepared in Comparative Example 2 has no catalytic effect under ultrasound due to severe agglomeration, while the ZnO@C catalysts with fixed morphology (nanowires) prepared in Examples 1, 4 and 5 have significant piezoelectric catalytic effects, proving that under constant annealing time, adjusting the temperature can improve the piezoelectric catalytic effect by controlling the morphology of the ZnO@C catalyst. Among them, the ZnO@C catalyst annealed at 300°C for 60 minutes has the highest degradation efficiency for tetracycline, reaching 90% in 3 minutes and finally 94%.
[0061] (2) Performance test of piezoelectric catalytic degradation of tetracycline by ZnO@C piezoelectric film
[0062] The piezoelectric catalytic degradation of tetracycline by the ZnO@C piezoelectric film prepared in Example 6 was used to study the effect of piezoelectric catalytic degradation of tetracycline at different flow rates. The specific steps are as follows: the piezoelectric film is sealed in an integrated plastic filter holder, and different flow rates are adjusted by a peristaltic pump. Samples are taken at 1, 3, 5, 10, 20 and 30 minutes respectively. The absorbance of TC in the solution is measured at a wavelength of 355 nm using a UV-visible spectrophotometer (SDPTOP, UV2400). The results are shown in Figure 2. Fig.11 As shown in the figure, the degradation efficiency reaches the maximum value when the flow rate is 160 ml / min. Under this condition, the degradation rate can reach 75% in 5 minutes and more than 92.7% in 30 minutes.
[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. Application of a carbon-coated zinc oxide piezoelectric film in the field of wastewater remediation, characterized in that: The carbon-coated zinc oxide piezoelectric film utilizes the vibration energy of water flow to convert mechanical energy into electrical energy, which is used for piezoelectric catalytic degradation and treatment of organic pollutant wastewater; The preparation method of the carbon-coated zinc oxide piezoelectric film comprises the following steps: adding the carbon-coated zinc oxide piezoelectric catalyst to the casting solution and stirring to obtain a mixture, injecting the mixture into a glass dish, performing phase conversion with deionized water, and then taking out the film, washing it and performing vacuum drying; The preparation method of the carbon-coated zinc oxide piezoelectric catalyst comprises the following steps: uniformly grinding zinc acetate dihydrate, then transferring it to an alumina crucible, annealing it in a muffle furnace at a certain temperature and time, and then taking it out and grinding it again; The annealing temperature is 300° C., and the annealing time is 60 min, 90 min or 120 min; Alternatively, the annealing temperature is 350° C. or 400° C., and the annealing time is 60 min.
2. The use according to claim 1, characterized in that: The method for preparing the casting solution is to dissolve the precursor in an organic solvent, and add a hydrophilic agent and a porogen to form a uniform colloid.
3. The use according to claim 1, characterized in that: In the method for preparing the carbon-coated zinc oxide piezoelectric film, the mass percentage of the carbon-coated zinc oxide piezoelectric catalyst in the mixture is 5% to 30%.
4. The use according to claim 1, characterized in that: The vacuum drying is carried out at a temperature of 50-90° C. and for a time of 12-24 hours.
Citation Information
Patent Citations
Firework-shaped nano-ZnO photocatalyst prepared based on one-step calcination method and method thereof
CN104998633A
A ZnO photocatalytic material modified with porous carbon and a preparing method thereof
CN107362789A
Method for piezoelectric catalytic degradation of organic dye by using low-dimensional zinc oxide nano material
CN112209476A